Antara Efisiensi Dan Kekhawatiran: Menimbang Dampak Kecerdasan Buatan Terhadap Dinamika Dan Etika Lingkungan Kerja Pada PT. Colab Prosperity Jaya - Raihan Kenai Ilyasa; Mochamad Abdul Faiz (Jurnal Manajemen Bisnis Digital Terkini, 2024)
This study examines the impact of artificial intelligence (AI) on the dynamics and ethics of the workplace environment at PT COLAB PROSPERITY JAYA, a company engaged in the coconut product export industry. Using a qualitative approach, this research involved in-depth interviews with employees at various levels to explore how AI affects work efficiency, decision-making, ethical issues, and employee interactions. The results indicate that AI improves efficiency and supports decision-making with accurate data. However, there are serious ethical concerns, especially regarding data privacy and algorithmic bias. Furthermore, although AI facilitates task management, it also has the potential to reduce social interactions that are crucial for creativity and teamwork. This study suggests the need for stronger policies and ethical training to ensure that AI is integrated in a responsible and fair manner, emphasizing the importance of balancing the benefits of technology with human values in the development and application of AI in the workplace.